2011
DOI: 10.1016/j.adolescence.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Relational and social‐cognitive correlates of early adolescents’ forgiveness of parents

Abstract: This study examined how mother and father-child relationship quality and marital forgiveness were related to early adolescents' forgiveness of mothers and fathers. Adolescents' social-cognitive skills (empathy and emotional regulation) and parents' forgiveness of child were examined as mediators. Mother, father, and child self-reported questionnaires and observational data were taken from Time 1 and Time 3 (two years later) of the Flourishing Families Project, and included 334 two-parent families with an early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
7
0
3
Order By: Relevance
“…This may suggest that the highly empathetic youth tend to focus on others’ experiences in a fairly objective or unselfish manner and more likely to forgive offenders instead of taking revenge and avoidance ( Toussaint and Webb, 2005 ). Christensen et al (2011) found that empathy is the most salient predictor of forgiveness in the parent–child relationship. A study of forgiveness intervention on female aggressive victims showed that, compared with other groups, victims in the forgiveness intervention group had a significant improvement in empathy and academic performance and a significant reduction in anger, hostility attribution, and delinquent behavior ( Park et al, 2013 ).…”
Section: Discussionmentioning
confidence: 97%
“…This may suggest that the highly empathetic youth tend to focus on others’ experiences in a fairly objective or unselfish manner and more likely to forgive offenders instead of taking revenge and avoidance ( Toussaint and Webb, 2005 ). Christensen et al (2011) found that empathy is the most salient predictor of forgiveness in the parent–child relationship. A study of forgiveness intervention on female aggressive victims showed that, compared with other groups, victims in the forgiveness intervention group had a significant improvement in empathy and academic performance and a significant reduction in anger, hostility attribution, and delinquent behavior ( Park et al, 2013 ).…”
Section: Discussionmentioning
confidence: 97%
“…still scant" (p. 348). Forgiveness is often regarded as requiring the ability to attend to, regulate, and repair emotional responses, and to therefore necessitate abstract thought and emotional management skills commonly accepted as only developing in adolescence (e.g., Rizkalla et al, 2008;Christensen et al, 2011). However, children are able to intuit and interpret emotions, and forgiving includes replacing negative other-oriented with positive other-oriented emotions (Worthington et al, 2007).…”
Section: Forgiveness In Childrenmentioning
confidence: 99%
“…Vztah k rodičům je specifický svou primární nevyrovnaností. Do všech ostatních vztahů dítě vstupuje už s určitou sociální, vztahovou a jazykovou výbavou, kdežto v dynamice vztahu k rodičům tuto výbavu teprve získává (Christensen, Padilla -Walker, Busby, Hardy, & Day, 2011). Člověk zároveň přirozeně neočekává zranění ze strany rodičů.…”
Section: Je Schopnost Odpouštět Univerzální Nebo Závislá Na Kontextu?unclassified
“…Dospívající se podle nich učí od svých rodičů odpouštět dvojím způsobem. Jednak tím, že vidí odpuštění v jejich vztahuschopnost otce odpouštět manželce pozitivně korelovala s odpuštěním u dospívajícího -a jednak tím, že jemu samotnému bývá odpouštěno -schopnost maminky odpouštět dospívajícím pozitivně korelovala s jejich odpuštěním v dalších letech (Christensen, Padilla -Walker, Busby, Hardy, & Day, 2011). Odpuštění v rodině také zkoumali Maio, Thomas, Fincham a Carnelley (2008).…”
Section: Starší šKolní Věk (12-15)unclassified
See 1 more Smart Citation